(1)
Ifp(x)=x2-5x-6, then find the values of p(1), p(2),p(3),p(0),p(-1),p(-2), p(-3).
If p(m) = m2 - 3m+ 1, then find the value of p(1) and p(-1).
Answers
Step-by-step explanation:
p(x) = x²-5x -6
Putting p value is 1
p(1) = (1)²-5-6
p(1)= 1-11
p(1) = -10
Putting p value is 2
p(2) = (2)²-10-6
p(2) = 4 -26
p(2) = -22
Putting p value is 3
p(3) = (3)²-15-6
p(3) = 9-21
p(3) = -12
Putting p value is 0
p(0) = 0-0-6
p(0) = -6
Putting p value is -1
p(-1) = (-1)²+5-6
p(-1) = 1 -1
p(-1)=0
Putting p value is -2
p(-2) = (-2)²+10-6
p(-2) = 4+10-6
p(-2) = 8
Putting p value is -3
p(-3) = (-3)³+15-6
p(-3) = 9 +15-6
p(-3)=18
p(m) = m²-3m+1
Putting m value is 1
p(1) = (1)²-3+1
p(1)=1-3+1
p(1)=-1
Putting m value is -1
p(-1) = (-1)²+3+1
p(-1)= 1+3+1
p(-1)= 5
Hope it will help you mate !!
p(x)=x2-5x-6 sol:
-9,-12,-15,-6,-3,0,3
p(m)=m2-3m+1
0,2
Step-by-step explanation:
p(x)=x2-5x-6
p(1)=(1)2-5(1)-6
=2-5-6
=-9
p(2)=(2)2-5(2)-6
=4-10-6
=-12
p(3)=(3)2-5(3)-6
=6-15-6
=-15
p(0)=(0)2-5(0)-6
=-6
p(-1)=(-1)2-5(-1)-6
=-2+5-6
-3
p(-2)=(-2)2-5(-2)-6
=-4+10-6
=0
p(-3)=(-3)2-5(-3)-6
-6+15-6
=3
p(m)=m2-3m+1
p(x)=1,-1
p(1)=(1)2-3(1)+1
=2-3+1
=0
p(-1)=(-1)2-3(-1)+1
-2+3+1
=2